Analisis Persepsi Orang Tua Terhadap Penggunaan Obat Sirup Dengan Kejadian Gagal Ginjal Akut Pada Anak - Lisa Ardianti; Syarifah Masthura; Cut Oktaviana (Pusat Riset dan Inovasi Nasional, 2023)
Children's syrup medicine risks containing Ethylene Glycol (EG) and Diethylene Glycol (DEG) contaminants, which are the solvents for syrup medicine. The syrup contains the risk of acute kidney failure. It may be poisoned because it has diethylene glycol. This condition may influence the parents' perception as the person who allowed the children to consume that medicine, which may affect their health. This research aimed to analyze the students' perception toward the use of syrup medication with the incidence of acute kidney failure among children in Gampong Jawa of Banda Aceh. This quantitative research used a correlative descriptive method using a cross-sectional design. The sample in this research was 86 parents who have children aged 0-6 years old which was chosen using total sampling. This research was conducted from July 8th to 13th, 2023. The result of the statistic test using the chi-square test obtained that the p-value was 0.042. It was concluded that Ho was rejected and Ha was accepted, which means there was a correlation between parents' perception and the use of syrup medication.